FACTORS OF FOREIGN LABOR MIGRATION IN UZBEKISTAN (Journal of Multidisciplinary Sciences and Innovations, 2025)
The article analyzes the essence, main directions, causes and consequences of external labor migration in Uzbekistan. It also examines the economic, social and psychological problems faced by labor migrants.